(untitled) (Quinto Sol, 2021)
This article analyzes the numbers of women elected to hold positions in the provincial legislatures and the constitutional conventions of three new provinces since the first election in which they voted until the fall of the Juan Domingo Perón government. The elections of 1951, 1953, 1954 and 1955 are examined. At the same time, the figures obtained in these elections are compared with the national ones and those stipulated years later with the Quota and Gender Parity law.